THE INTRODUCTION OF WAQF INTO FRACTIONAL AND FULL RESERVE BANKING SYSTEMS TO ACHIEVE ECONOMIC STABILITY - Omer Faruk Tekdogan (Journal of Islamic Monetary Economics and Finance, 2020)
Fractional reserve banking is a system in which banks extend loans by creating credit/deposit money, and which can be considered the basis of modern financial architecture. Nevertheless, it has been criticised because of its inherently weak and fragile structure in terms of financial and economic stability. As a theoretical solution, full reserve banking has been supported in academic circles, with many technical variations. However, Islamic economics can help to maintain financial and economic stability with its original institution of waqf. Besides performing social functions, waqf also undertakes financial intermediary functions and preserved financial stability in the period of the Ottoman Empire. The purpose of this study is to examine the effects of fractional reserve banking on economic stability and to make a comparison with full reserve banking to observe its potential as an alternative solution. The study also examines the efficiency of the Islamic social and economic institution of waqf in maintaining economic stability in both fractional and full reserve systems. The results demonstrate that full reserve banking is a promising approach to maintaining economic stability and that waqf enhances economic stability in both banking systems.